Gambaran Determinan Pemberian ASI Eksklusif pada Ibu dengan Bayi Usia 6-24 Bulan - Maesaroh, Siti; Kristianingsih, Ani; Anggraini, Heni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2018)
One indicator to know the health status in a country can be seen from the high Infant Mortality Rate (IMR). The main cause of infant death is due to respiratory tract infections and diarrhea. According to the World Health Organization (WHO) that acute pneumonia cases, 55 percent of infant deaths due to diarrhea due to lack of exclusive breastfeeding in the first six months at the beginning of the baby's life. The success of exclusive breastfeeding programs can create a golden generation (golden Period) which at that age happens optimal growth process. This study aims to determine the description of the determinant of exclusive breastfeeding in the mother in Wonosari Village, Subdistrict of Gadingrejo. This research type is quantitative research by using descriptive method. The samples used were 92 mothers who had babies 6-24 months old. From the results of the study, it was found that the distribution of respondents who gave exclusive breastfeeding as many as 48 people (52.2 percent), and who did not give exclusive milk as many as 44 people (47.8 percent). Respondents have a good knowledge about exclusive breastfeeding as many as 63 people (68.5 percent). Respondents had a positive attitude toward exclusive breastfeeding of 33 people (35.9 percent). Respondents who received husband support in exclusive breastfeeding as many as 26 people (28.3 percent). Respondents who received the support of health officers to exclusive breastfeeding were 56 people (60.9 percent). The results of this study can be used as guidelines to formulate strategies in providing information about health, especially about the importance of exclusive breastfeeding in an effort to increase the achievement of exclusive breastfeeding coverage to 100 percent, so that by itself will reduce the IMR.